2018
DOI: 10.1007/s10142-017-0585-5
|View full text |Cite|
|
Sign up to set email alerts
|

A large-scale multiomics analysis of wheat stem solidness and the wheat stem sawfly feeding response, and syntenic associations in barley, Brachypodium, and rice

Abstract: The wheat stem sawfly (WSS), Cephus cinctus Norton (Hymenoptera: Cephidae), is an important pest of wheat and other cereals, threatening the quality and quantity of grain production. WSS larvae feed and develop inside the stem where they are protected from the external environment; therefore, pest management strategies primarily rely on host plant resistance. A major locus on the long arm of wheat chromosome 3B underlies most of the variation in stem solidness; however, the impact of stem solidness on WSS feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 85 publications
(89 reference statements)
1
35
0
Order By: Relevance
“…Tricetin activates lignin biosynthesis in secondary cell wall production ( Moheb et al 2013 ). However, C. cinctus feeding downregulated the synthesis of these metabolites, perhaps supporting the idea that these larvae disrupt signals and limit subsequent synthesis of these metabolites ( Biyiklioglu et al 2018 ). Cultivated barley has lost the biosynthetic capability to produce DIMBOA ( Nomura et al 2002 , Grun et al 2005 ), but there are other groups of compounds, such as flavonoids and alkaloids that may be synthesized to ward off insect pests ( Balmer et al 2013 ).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Tricetin activates lignin biosynthesis in secondary cell wall production ( Moheb et al 2013 ). However, C. cinctus feeding downregulated the synthesis of these metabolites, perhaps supporting the idea that these larvae disrupt signals and limit subsequent synthesis of these metabolites ( Biyiklioglu et al 2018 ). Cultivated barley has lost the biosynthetic capability to produce DIMBOA ( Nomura et al 2002 , Grun et al 2005 ), but there are other groups of compounds, such as flavonoids and alkaloids that may be synthesized to ward off insect pests ( Balmer et al 2013 ).…”
mentioning
confidence: 74%
“…One major factor causing larval mortality is host plant antibiosis in barley and certain wheat cultivars ( Wallace and McNeal 1966 , Buteler et al 2015 , Varella et al 2018 ). Some defense related secondary metabolites, such as DIMBOA (2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one), tricetin, and lignin are downregulated in C. cinctus -infested wheat stems ( Biyiklioglu et al 2018 ), indicating that these compounds are synthesized in response to and have a negative effect on C. cinctus . Although cultivated barley has lost the ability to biosynthesize DIMBOA ( Nomura et al 2002 , Grun et al 2005 ), other groups of defensive compounds, such as benzoxazinoids, flavonoids, and alkaloids can be synthesized to ward off insect pests ( Balmer et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that miRNAs are involved in the drought stress of wheat [30,31] or dehydration stress in Triticeae [32]. A large-scale multiomics analysis showed that miRNAs involved the potential regulatory in wheat stem sawfly [33]. Shen et al reported that some miRNAs of Oryza sativa responded to a drought, salt and the cold [34].…”
Section: Introductionmentioning
confidence: 99%
“…Border modifications or the use of seed blends to limit the amount of solid stem wheat planted have had some success in limiting wheat stem sawfly damage; however, planting the entire crop to a solid stem variety remains the best option ( Beres et al 2009 ). Recent molecular investigations into barley’s resistance to wheat stem sawfly larvae and the characterization of wheat’s response to wheat stem sawfly larval feeding have the potential to create new mechanisms of plant resistance against the wheat stem sawfly ( Biyiklioglu et al 2018 , Varella et al 2018 ).…”
mentioning
confidence: 99%